An acorn starch and a method for modifying the same
Patent Information
- Application Number
- CN202611236226.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]本发明的主要目的是提出一种橡子淀粉及其改性方法,旨在解决现有技术中橡子淀粉冻融稳定性较差的问题
[0015]本发明的技术方案中,通过动态高压微射流方法对橡子淀粉进行纯物理改性,能够显著降低橡子淀粉的析水率,从而提升橡子淀粉的冻融稳定性;进一步对动态高压微射流改性后的橡子淀粉进行超高压处理且控制超高压压力P<600MPa,能够进一步提升橡子淀粉的冻融稳定性,进一步控制超高压压力P在300MPa<P<600MPa区间内时,橡子淀粉的持水性能得到显著提升。
Smart Images

Figure CN122878458A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of acorn starch modification technology, and particularly to an acorn starch and its modification method. Background Technology
[0002] Acorn starch is a unique plant starch that is abundant, green, and renewable. It has advantages such as high gel strength, low gelation temperature, and high resistant starch content, and has good application potential in food thickeners, gel products, and biodegradable materials.
[0003] However, natural acorn starch has drawbacks such as poor swelling properties, instability under polar conditions, easy aging, and poor freeze-thaw stability, which limit its diversified application in the modern food industry. Summary of the Invention
[0004] The main objective of this invention is to propose an acorn starch and its modification method, aiming to solve the problem of poor freeze-thaw stability of acorn starch in the prior art.
[0005] To achieve the above objectives, the present invention proposes a method for modifying acorn starch, the method comprising the following steps: S1. Provide acorn starch; S2. Mix the acorn starch with water to obtain a starch milk; S3. The starch milk is subjected to dynamic high-pressure microjet treatment, centrifuged and dried to obtain modified acorn starch.
[0006] In one embodiment, step S3 includes: S31. The starch milk is subjected to dynamic high-pressure microjet treatment, centrifuged and dried to obtain the first starch. S32. Mix the first starch with water to obtain a starch suspension; S33. The starch suspension is subjected to ultra-high pressure treatment and dried to obtain modified acorn starch. The pressure P of the ultra-high pressure treatment is in the range of 0 MPa < P < 600 MPa.
[0007] In one embodiment, in step S33, the pressure P of the ultra-high pressure treatment is in the range of 300MPa < P < 600MPa.
[0008] In one embodiment, in step S31: The pressure of the dynamic high-pressure microjet treatment is 75~85MPa; The dynamic high-pressure microjets treatment time is 3-10 min; and / or, The dynamic high-pressure microjet treatment is performed 1 to 5 times.
[0009] In one embodiment, in step S32, the starch in the starch suspension has a mass fraction of 15% to 25%.
[0010] In one embodiment, in step S33: The ultra-high pressure treatment time is 0.5~1.5h; and / or, The drying temperature is 35~45℃.
[0011] In one embodiment, in step S2, the starch in the starch milk has a mass fraction of 8% to 12%.
[0012] In one embodiment, step S1 includes: S11. Provide acorns, grind the acorns into powder, soak them in water, take the sedimentation layer, and obtain the first acorn powder; S12. Soak the first acorn powder in water at 45℃~50℃, take the sedimentation layer, and obtain the second acorn powder. S13. The second acorn powder is soaked in sodium carbonate solution and hydrogen peroxide solution in sequence, and the sediment layer is collected to obtain the third acorn powder. S14. Soak the third acorn powder in water, centrifuge, and dry to obtain the acorn starch.
[0013] In one embodiment, in step S11, the soaking in clean water is performed 2 to 3 times; and / or, In step S12, the soaking time in clean water is 12-24 hours; and / or, In step S13, the concentration of the sodium carbonate solution is 0.4%~0.6%, and the soaking time with the sodium carbonate solution is 4~12 hours; and / or, In step S13, the concentration of the hydrogen peroxide solution is 0.8-1.2%, and the solution is used to soak the patient at 35-45°C for 4-5 hours; and / or, In step S14, the soaking time in clean water is 10-12 hours.
[0014] The present invention also provides an acorn starch, which is prepared by the aforementioned method for modifying acorn starch.
[0015] In the technical solution of this invention, acorn starch is physically modified by dynamic high-pressure microjet method, which can significantly reduce the water separation rate of acorn starch and thus improve its freeze-thaw stability. Furthermore, the acorn starch modified by dynamic high-pressure microjet is subjected to ultra-high pressure treatment and the ultra-high pressure P is controlled to be less than 600 MPa, which can further improve the freeze-thaw stability of acorn starch. When the ultra-high pressure P is controlled to be within the range of 300 MPa < P < 600 MPa, the water holding capacity of acorn starch is significantly improved. Attached Figure Description
[0016] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0017] Figure 1 These are scanning electron microscope images of the acorn starch prepared in Examples 1-5 and Comparative Example 1 of the present invention; Figure 2 The XRD patterns are of the acorn starch prepared in Examples 1-5 and Comparative Example 1 of this invention. Figure 3 The polarization images are of the acorn starch prepared in Examples 1-5 and Comparative Example 1 of this invention. Figure 4 The infrared spectra of acorn starch prepared in Examples 1-5 and Comparative Example 1 of this invention are shown below. Figure 5 The particle size distribution diagrams are shown for the acorn starch prepared in Examples 1-5 and Comparative Example 1 of this invention. Figure 6 The graph shows the water-holding capacity of the acorn starch prepared in Examples 1-5 and Comparative Example 1 of this invention. Figure 7 The graph shows the water separation rate of the acorn starch prepared in Examples 1-5 and Comparative Example 1 of this invention. Figure 8 The viscosity curves of the acorn starch prepared in Examples 1-5 and Comparative Example 1 of this invention are shown.
[0018] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially. Furthermore, the meaning of "and / or" throughout the text includes three parallel solutions; for example, "A and / or B" includes solution A, or solution B, or a solution where both A and B are satisfied simultaneously. In addition, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] Natural acorn starch has drawbacks such as poor swelling properties, instability under polar conditions, easy aging, and poor freeze-thaw stability, which limit its diversified application in the modern food industry.
[0021] In view of this, the present invention proposes a method for modifying acorn starch, the method comprising the following steps: Step S1: Provide acorn starch; Step S2: Mix the acorn starch with water to obtain a starch slurry; Step S3: The starch milk is subjected to dynamic high-pressure microjet treatment, centrifuged and dried to obtain modified acorn starch.
[0022] In the technical solution of this invention, the acorn starch is physically modified by a dynamic high-pressure microjet method, which can significantly reduce the water separation rate of acorn starch and thus improve its freeze-thaw stability. Furthermore, the acorn starch modified by dynamic high-pressure microjet is subjected to ultra-high pressure treatment and the ultra-high pressure P is controlled to be less than 600 MPa, which can further improve the freeze-thaw stability of acorn starch. Moreover, when the ultra-high pressure P is in the range of 300 MPa < P < 600 MPa, the water holding capacity of acorn starch is significantly improved.
[0023] The pressure of the dynamic high-pressure microjet method can be 50MPa, 60MPa, 80MPa, 100MPa or even higher, and the preferred pressure of the dynamic high-pressure microjet method is 80MPa.
[0024] It should be noted that in this paper, Dynamic High-Pressure Microfluidization (DHPM) is a method for pre-modifying starch by relying on strong shearing, cavitation and impact to break the surface of starch granules and disturb the internal ordered structure, without destroying the basic crystal form of starch. It can be achieved by an AH-2010 ultra-high pressure microfluidization homogenizer.
[0025] However, the effect of simple physical modification on the regulation of acorn starch structure and its functions such as water retention and freeze-thaw stability is limited. In some embodiments, step S3 includes: Step S31: The starch milk is subjected to dynamic high-pressure microjet treatment, centrifuged and dried to obtain the first starch; Step S32: Mix the first starch with water to obtain a starch suspension; Step S33: The starch suspension is subjected to ultra-high pressure treatment and dried to obtain modified acorn starch; The pressure P of the ultra-high pressure treatment is in the range of 0 MPa < P < 600 MPa.
[0026] In the technical solution of this invention, after the acorn starch is subjected to dynamic high-pressure microjet treatment, the acorn starch completes the first physical modification to obtain the first starch, at which point the freeze-thaw stability of the first starch is significantly improved; when the first starch suspension is subjected to ultra-high pressure treatment, the acorn starch completes the second physical modification. The pressure of the ultra-high pressure treatment can be 0.1MPa, 10MPa, 100MPa, 300MPa or 500MPa. Controlling the ultra-high pressure P within the range of 0MPa < P < 600MPa can ensure that the freeze-thaw stability of the acorn starch is further improved.
[0027] It should be noted that in this article, ultra-high pressure (HPP) changes the non-covalent chemical bonds of starch through physical pressure, but has little effect on the covalent chemical bonds. It can be achieved using HPP.L2-700 / 1 ultra-high pressure equipment.
[0028] In some embodiments, in step S33, the pressure P of the ultra-high pressure treatment ranges from 300MPa < P < 600MPa.
[0029] In the technical solution of this invention, after the acorn starch is subjected to dynamic high-pressure microjet treatment, the acorn starch completes the first physical modification to obtain the first starch. At this time, the freeze-thaw stability of the first starch is significantly improved, but the water-holding capacity is not significantly changed. When the first starch suspension is subjected to ultra-high pressure treatment, the acorn starch completes the second physical modification. The pressure of ultra-high pressure treatment can be 310MPa, 400MPa, 500MPa or 550MPa. Controlling the ultra-high pressure P within the range of 300MPa < P < 600MPa can ensure good freeze-thaw stability of the acorn starch, while significantly improving the water-holding capacity.
[0030] In some embodiments, in step S31: the pressure of the dynamic high-pressure microjet treatment is 75-85 MPa; the time of the dynamic high-pressure microjet treatment is 3-10 min; and / or, the number of dynamic high-pressure microjet treatments is 1-5 times. That is, the pressure of the dynamic high-pressure microjet treatment can be 75 MPa, 80 MPa, or 85 MPa; the time of the dynamic high-pressure microjet treatment can be 3 min, 5 min, or 10 min; and the number of dynamic high-pressure microjet treatments can be 1 time, 3 times, or 5 times. Controlling the above conditions within a suitable range can ensure that the acorn starch is sufficiently modified, thereby significantly improving its freeze-thaw stability.
[0031] In some embodiments, in step S32, the starch in the starch suspension has a mass fraction of 15% to 25%. That is, the mass fraction of starch can be 15%, 20%, or 25%, and controlling its mass fraction within the above range can ensure that the starch is sufficiently modified.
[0032] In some embodiments, in step S33: the ultra-high pressure treatment time is 0.5~1.5h; and / or, the drying temperature is 35~45℃. The ultra-high pressure treatment time can be 0.5h, 1h, or 1.5h, and the drying temperature can be 35℃, 40℃, or 45℃. That is, when the ultra-high pressure treatment pressure is 0MPa < P < 600MPa, and the ultra-high pressure treatment time and drying temperature are controlled within the above ranges, the acorn starch can be sufficiently modified in the second stage, further improving its freeze-thaw stability, and the low drying temperature can ensure that the acorn starch does not undergo gelatinization or other changes.
[0033] In some embodiments, in step S2, the starch in the starch milk has a mass fraction of 8% to 12%. That is, the mass fraction of starch can be 8%, 10%, or 12%, and controlling its mass fraction within the above range can ensure that the starch is sufficiently modified.
[0034] In some embodiments, step S1 includes: Step S11: Provide acorns, grind the acorns into powder, soak them in water, take the sedimentation layer, and obtain the first acorn powder; Step S12: Soak the first acorn powder in water at 45℃~50℃, take the sedimentation layer, and obtain the second acorn powder; Step S13: Soak the second acorn powder in sodium carbonate solution and hydrogen peroxide solution in sequence, take the sediment layer, and obtain the third acorn powder; Step S14: Soak the third acorn powder in water, centrifuge, and dry to obtain the acorn starch.
[0035] In the technical solution of the present invention, in step S11, the acorns are ground and then soaked in water to remove water-soluble impurities from the acorn powder by utilizing the concentration difference, thus obtaining first acorn powder; in step S12, the first acorn powder can permeate and swell starch granules at 45~50℃, thereby facilitating subsequent separation to obtain second acorn powder; in step S13, sodium carbonate solution provides an alkaline environment, which can promote the alkaline hydrolysis of proteins in the second acorn powder to generate soluble peptides and be removed, and at the same time can cause lipids in the second acorn powder to undergo a chemical reaction to generate soluble soaps and be removed; subsequently, hydrogen peroxide solution can be used to remove pigments and other colored impurities in the second acorn powder, thereby obtaining third acorn powder; in step S14, soaking the third acorn powder in water can wash away residual sodium carbonate and hydrogen peroxide and their reaction products, thereby obtaining acorn starch with high purity.
[0036] In some embodiments, in step S11, the soaking in clean water is performed 2 to 3 times; and / or, in step S12, the soaking time in clean water is 12 to 24 hours; and / or, in step S13, the concentration of the sodium carbonate solution is 0.4% to 0.6%, and the soaking time in the sodium carbonate solution is 4 to 12 hours; and / or, in step S13, the concentration of the hydrogen peroxide solution is 0.8% to 1.2%, and the soaking time in the hydrogen peroxide solution is 4 to 5 hours at 35 to 45°C; and / or, in step S14, the soaking time in clean water is 10 to 12 hours. That is, the number of times the acorn powder is soaked in water can be 2 or 3 times; the soaking time for the first acorn powder in water can be 12h, 20h, or 24h; the concentration of the sodium carbonate solution can be 0.4%, 0.5%, or 0.6%; the soaking time using the sodium carbonate solution can be 4h, 8h, or 12h; the concentration of the hydrogen peroxide solution can be 0.8%, 1.0%, or 1.2%; the soaking temperature using the hydrogen peroxide solution can be 35℃, 40℃, or 45℃; the soaking time using the hydrogen peroxide solution can be 4h, 4.5h, or 5h; and the soaking time for the third acorn powder in water can be 10h, 11h, or 12h. Controlling these parameters within a suitable range ensures that the obtained acorn starch has fewer impurities and higher purity, which is beneficial for subsequent modification treatment.
[0037] The present invention also provides an acorn starch, which is prepared by the aforementioned method for modifying acorn starch. Therefore, this acorn starch possesses all the beneficial effects of the aforementioned method for modifying acorn starch, which will not be elaborated upon here.
[0038] The technical solution of the present invention will be further described in detail below with reference to specific embodiments and accompanying drawings. It should be understood that the following embodiments are only used to explain the present invention and are not intended to limit the present invention.
[0039] Example 1 A method for modifying acorn starch includes the following steps: (1) Extracting starch from acorns: Grind acorns into powder and soak them in water. Change the water every 2 hours (repeat 3 times). Take the sedimented starch layer, which is the first acorn powder. Then add five times the volume of water to the first acorn powder and soak it at 45°C for 12 hours. Change the water and continue soaking for 24 hours. Take the sedimented starch layer, which is the second acorn powder. Soak the second acorn powder in two times the volume of Na2CO3 solution with a mass fraction of 0.5% for 3 times. The soaking time for the 3 times is 4 hours, 6 hours and 12 hours respectively. Then soak it in five times the volume of H2O2 solution with a mass fraction of 1.0%. Bleach it continuously with stirring at pH 7 and 40°C for 5 hours. Then let it stand for 6 hours and take the sedimented layer to obtain the third acorn powder. Soak the third acorn powder in water for 12 hours, centrifuge at 4000 rpm for 10 minutes, dry it at 40°C to constant weight, pulverize it and pass it through a 100-mesh steel sieve to obtain acorn starch.
[0040] (2) Mix acorn starch and water to prepare a starch milk with a mass fraction of 10%. The starch milk is subjected to dynamic high pressure microjet treatment. The pressure of dynamic high pressure microjet treatment is 80 MPa. The number of dynamic high pressure microjet treatments is 5 times, and the treatment time is 5 min each time. After the treatment is completed, it is centrifuged at 4000 rpm for 10 min, dried at 40℃ to constant weight, and ground through a 100-mesh sieve to obtain the first starch.
[0041] (3) Mix the first starch with water to prepare a starch suspension with a mass concentration of 20%. Place the starch suspension in a 150 mL plastic bottle for ultra-high pressure treatment (hydrostatic pressure). The pressure of ultra-high pressure treatment is 100 MPa and the time of ultra-high pressure treatment is 1 h. After the treatment is completed, dry it at 40℃ to constant weight and grind it through a 100-mesh sieve to obtain the modified acorn starch.
[0042] Example 2 The difference between Example 2 and Example 1 is that: The pressure for ultra-high pressure processing is 300 MPa.
[0043] Example 3 The difference between Example 3 and Example 1 is that: The pressure for ultra-high pressure processing is 500 MPa.
[0044] Example 4 The difference between Example 4 and Example 1 is that: The pressure for ultra-high pressure processing is 600 MPa.
[0045] Example 5 The difference between Example 5 and Example 1 is that: The pressure of the ultra-high pressure treatment is 0 MPa, that is, step (3) is not performed. The first starch in step (2) is the modified acorn starch.
[0046] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that: Without performing steps (2) and (3), natural acorn starch is obtained.
[0047] Performance testing 1. Scanning electron microscopy (SEM) was performed on the natural or modified acorn starch in Examples 1-5 and Comparative Example 1. The specific steps were as follows: a small amount of acorn starch was directly adhered to conductive adhesive, and gold was sputtered onto it for 45 seconds at a speed of 10 mA. The accelerating voltage for morphology imaging was 5 kV, and for energy dispersive spectroscopy (EDS) mapping, it was 20 kV. An SE2 secondary electron detector was used. The results are as follows: Figure 1 As shown.
[0048] Figure 1 In the diagram, a is a scanning electron microscope (SEM) image of acorn starch in Comparative Example 1, b is a scanning electron microscope (SEM) image of modified acorn starch in Example 5, c is a scanning electron microscope (SEM) image of modified acorn starch in Example 1, d is a scanning electron microscope (SEM) image of modified acorn starch in Example 2, e is a scanning electron microscope (SEM) image of modified acorn starch in Example 3, and f is a scanning electron microscope (SEM) image of modified acorn starch in Example 4.
[0049] Figure 1 Image a shows that natural acorn starch granules are elliptical or irregularly polyhedral in shape, with a relatively smooth and intact surface, uneven size distribution, and a small number of fragments, exhibiting typical characteristics of natural starch granules. Figure 1 From b, c, d, e, and f, it can be seen that after dynamic high-pressure microjets are processed (corresponding to...) Figure 1 (b) and dynamic high-pressure microjets + ultra-high-pressure treatment (100 MPa, corresponding to...) Figure 1After treatment (c), the starch granules maintained their overall morphology, but slight indentations or increased roughness were observed on the granule surface. This is likely due to physical wear of the granule surface caused by the high shear force generated by Dynamic High Pressure Microjets (DHPM). When the pressure of the ultra-high pressure treatment was increased to 300 MPa and 500 MPa (corresponding to...), the overall morphology of the starch granules remained intact, but slight indentations or increased roughness were observed on the granule surface. This is likely due to physical wear caused by the high shear force generated by Dynamic High Pressure Microjets (DHPM). Figure 1 d and Figure 1 At pressure (e), some granules showed obvious collapse and adhesion, and the number of surface cracks increased, indicating that the high hydrostatic pressure had damaged the internal structure of the starch granules and reduced their integrity. When the ultra-high pressure treatment reached 600 MPa (corresponding to...),... Figure 1 During the process of pressure relief (f), the morphology of starch granules underwent drastic changes. The original granular structure almost completely disappeared, transforming into irregular blocky aggregates or lamellar structures. This indicates that the extreme high pressure of 600 MPa is sufficient to completely destroy the orderly arrangement of starch granules, induce starch to gelatinize or gel, and form new dense aggregates during the pressure relief process.
[0050] 2. X-ray diffraction (XRD) tests were performed on the natural or modified acorn starch in Examples 1-5 and Comparative Example 1. Specific parameters were: copper target, tube voltage and current of 40 kV and 40 mA respectively, scan rate of 10 min° / min, and scan range of 5-60°. The results are as follows: Figure 2 As shown.
[0051] Figure 2 In the legend, "acorn starch" refers to Comparative Example 1, "0 MPa" refers to Example 5, "100 MPa" refers to Example 1, "300 MPa" refers to Example 2, "500 MPa" refers to Example 3, and "600 MPa" refers to Example 4.
[0052] Depend on Figure 2It can be seen that the acorn starch in each group exhibited characteristic peaks around 15°, 17°, 18°, and 23°, showing typical A-type crystallization characteristic absorption peaks, indicating that the composite high-pressure treatment (i.e., dynamic high-pressure microfluidic treatment + ultra-high-pressure treatment) did not change the basic crystal type of acorn starch. With the increase of ultra-high-pressure treatment pressure, the intensity of the diffraction peaks changed significantly, reflecting the change in the internal crystallinity of the starch. According to the spectral data, the crystallinity (RC) of Comparative Example 1 was 44.16%. After DHPM treatment, the crystallinity decreased to 17.42%, indicating that the shear force generated by DHPM had caused some damage to the ordered structure inside the starch granules. Compared with Example 5, the crystallinity of Examples 1 and 2 showed an increasing trend, but still did not exceed that of Comparative Example 1. This may be due to the rearrangement of starch molecular chains damaged by the DHPM shear force caused by ultra-high pressure, the transformation of some amorphous regions into crystalline regions, or the relaxation of the original microcrystalline structure. When the ultra-high pressure reached 500 MPa, the crystallinity decreased to 21.34%, at which point the destructive effect of high-pressure mechanical force on crystallization became dominant. However, in Example 4, the crystallinity actually increased to 50.09%, even higher than that of Comparative Example 1. This anomaly may be attributed to the forced compression of starch molecular chains under extremely high pressure, inducing the formation of new ordered structures, or it may be because the high pressure caused severe retrogradation of starch after gelatinization during the depressurization process, resulting in a denser crystal structure.
[0053] 3. The polarized optical structure of the natural or modified acorn starch in Examples 1-5 and Comparative Example 1 was determined. The specific steps were as follows: a 10 g / L acorn starch powder suspension was prepared, and after preparation, the polarized crosses of the starch were observed under a polarizing microscope. The results are as follows: Figure 3 As shown.
[0054] Figure 3 In the diagram, a is the polarization pattern of acorn starch in Comparative Example 1, b is the polarization pattern of modified acorn starch in Example 5, c is the polarization pattern of modified acorn starch in Example 1, d is the polarization pattern of modified acorn starch in Example 2, e is the polarization pattern of modified acorn starch in Example 3, and f is the polarization pattern of modified acorn starch in Example 4.
[0055] Depend on Figure 3It is known that the characteristic "Maltese cross" pattern exhibited by starch granules under crossed polarized light is due to the anisotropy resulting from the difference between crystalline and amorphous regions with different densities and refractive indices. The starch granules of Comparative Example 1, Example 5, and Example 1 exhibit clear, bright, and complete Maltese crosses, indicating that they still maintain a highly ordered crystalline structure. As the ultra-high pressure increases to 300 MPa and 500 MPa, the number of complete crosses in the field of view decreases significantly, and the brightness of the remaining crosses weakens and the edges become blurred. This indicates that the ultra-high pressure treatment gradually destroys the radially ordered arrangement inside the starch granules, leading to a decrease in birefringence and partial gelatinization or amorphization transformation within the granules. Especially at an ultra-high pressure of 600 MPa, almost no obvious Maltese cross was observed in the field of view of Example 4, and the background showed a uniform dark field with only a few faint bright spots. This is because the extreme high pressure completely destroyed the radial layered crystalline framework of the natural starch granules, causing the complete granule shape to disappear and losing the structural basis for birefringence. This does not mean that the starch molecules are completely disordered. Under strong compression, the broken starch chains stacked disorderly and arranged locally to form a large number of irregular microcrystals, increasing the total proportion of microcrystals. Therefore, the crystallinity detected by XRD significantly increased. It is understandable that XRD and polarized structure represent particle-scale order and molecular-scale microcrystal proportion, respectively, and the results can complement and corroborate each other.
[0056] 4. Fourier transform infrared (IR) spectra of the natural or modified acorn starch in Examples 1-5 and Comparative Example 1 were determined. The specific steps were as follows: 1.0 mg of starch sample and 150 mg of anhydrous potassium bromide powder were weighed and rapidly ground in a mortar for 5 min. Then, the mixture was pressed into a mold, and the pressed mold was then placed in an infrared spectrometer for analysis in the wavenumber range of 4000-400 cm⁻¹. -1 The infrared spectra of the six groups of samples were compared, and the results are as follows: Figure 4 As shown.
[0057] Depend on Figure 4 It can be seen that no new characteristic absorption peaks were added to any starch sample, and the peak positions of functional groups did not shift. This indicates that microfluidic coupling with ultra-high pressure only changed the aggregated structure of starch molecules without destroying the covalent skeleton of starch glucose rings. It is a purely physical modification. This pattern is consistent with the characterization results of XRD showing no change in crystal form.
[0058] 3000-3600 cm -1The hydroxyl (OH) stretching vibration of starch reflects the degree of molecular hydrogen bond association. The IR spectra of Examples 5, 1, and 2 show that during the 0-300 MPa pressurization stage of ultra-high pressure (UHPP), the high pressure promotes the orderly rearrangement of the starch chains broken by DHPM, enhancing intermolecular hydrogen bond association. However, when the UHPP pressure reaches 500 MPa, this high-pressure mechanical force significantly breaks down the original hydrogen bond network of starch, resulting in a significant decrease in the intensity of the hydroxyl absorption peak. When the UHPP pressure reaches 600 MPa, the starch molecules are forcibly compressed, and free hydroxyl groups re-associate to form new hydrogen bonds, leading to a broadening of the peak shape. The phased trend of hydrogen bond changes corroborates the fluctuation pattern of XRD crystallinity.
[0059] Approximately 1640 cm -1 The bound water peak at the point continuously weakens as the ultra-high pressure treatment pressure increases. Ultra-high pressure removes the bound water inside the particles, exposing a large number of hydrophilic hydroxyl groups. This is the core microscopic reason for the significant improvement in the water-holding capacity of starch in Examples 3 and 4.
[0060] In 900-1200 cm -1 The fingerprint region showed significant changes in the relative intensity ratio and peak position of the CO / CC skeletal vibration peaks, indicating that ultra-high pressure (HHP) treatment disrupted the original crystalline structure of starch. This change in spectral intensity suggests that DHPM combined with HHP treatment induced alterations in the short-range ordered structure of starch, possibly due to high pressure inducing unwinding or recrystallization of starch molecular chains, thereby changing the ratio of crystalline to amorphous regions. This is corroborated by the XRD analysis results.
[0061] 5. The particle size of the natural or modified acorn starch in Examples 1-5 and Comparative Example 1 was determined. The specific steps were as follows: a 10 g / L acorn starch suspension was prepared. Test parameters: sample refractive index 1.520, shading range 10-15%, dispersant was pure water with a refractive index of 1.333, stirring speed 2000-3000 rpm, and the analytical model was general. Results are as follows. Figure 5 As shown in Table 1.
[0062] Table 1. Particle size characterization of starches prepared in Examples 1-5 and Comparative Example 1.
[0063] It should be noted that different lowercase letters in the same column of Table 1 indicate significant differences. P <0.05.
[0064] Depend on Figure 5 As shown in Table 1, the particle size parameter D in Examples 5, 1, and 2 is... 10 D 50 D [3,2]There was no significant difference between D and Comparative Example 1. 90 Compared to Comparative Example 1, a slight decrease was observed, with a slight reduction in particle size and a slight increase in specific surface area. This indicates that within this pressure range, only the surface layer of the starch granules was slightly abraded, and a small number of large particles broke into fine fragments. The overall particle dispersibility did not change significantly, corresponding to the morphological characteristics of intact particles with only a small amount of debris observed in the scanning electron microscope. When the ultra-high pressure was increased to 500 MPa, the particle size parameter D in Example 3... 10 D 50 D 90 Volume average diameter D [4,3] All particle sizes increased significantly, while the specific surface area decreased markedly. This is likely due to the agglomeration and adhesion of the broken starch particles under ultra-high pressure, forming larger aggregates and reducing the effective exposed area of the particles. When the ultra-high pressure treatment pressure reached 600 MPa, all particle size indicators increased sharply and significantly, with D... 50 It reached 643.33 μm, and the specific surface area dropped to the lowest in the entire group at only 13.94 m². 2 / kg, combined with scanning electron microscopy images, shows that the extremely high pressure squeezes, compacts and fuses all the broken starch granules into large flaky agglomerates, with the granules tightly stacked together and the specific surface area significantly reduced.
[0065] 6. The water-holding capacity of the natural or modified acorn starch in Examples 1-5 and Comparative Example 1 was determined. The specific steps were as follows: 1 g of starch and 5 mL of water were added to a centrifuge tube, stirred evenly, and allowed to stand at room temperature for 1 h. Then, the mixture was centrifuged at 3000 rpm for 15 min, and the weight of the precipitate was weighed. The calculation formula is shown below: Water holding capacity = (W2 - W1) / W1; In the formula: W1 represents the sample mass in g; W2 represents the precipitate mass in g.
[0066] The experiment was repeated three times, and the average value was taken. The results are as follows: Figure 6 As shown.
[0067] Depend on Figure 6It can be seen that with the increase of ultra-high pressure treatment, the water-holding capacity of starch shows a trend of first stabilizing and then rising sharply. Within the range of 0-300 MPa, the water-holding capacity of starch remained between 0.84-0.91 g / g, showing no significant difference compared to Comparative Example 1 (0.87 g / g). However, when the pressure increased to 500 MPa and 600 MPa, the water-holding capacity increased significantly, reaching 1.38 g / g and 2.69 g / g, respectively. This change is closely related to the aforementioned microstructure analysis. Combined with the particle size variation, it can be seen that the particle size and specific surface area of the samples in Examples 5, 1, and 2 are similar to those of natural acorn starch, with limited exposure of hydrophilic groups, thus resulting in no significant improvement in water-holding capacity. The 500 MPa ultra-high pressure treatment causes the broken small particles to stick together to form loose aggregates, creating a large number of pores inside that can accommodate external water molecules, thus significantly improving water retention. When the ultra-high pressure treatment pressure reaches 600 MPa, the particles are completely squeezed and fused into dense, large, sheet-like aggregates. The pores are compacted, and the specific surface area is reduced to a minimum. However, the natural starch crystals are completely disintegrated, and the hydrophilic hydroxyl groups are fully exposed. There are still a large number of microscopic water absorption channels between the stacked sheets, and the water retention capacity finally reaches its peak.
[0068] 7. The freeze-thaw stability of the natural or modified acorn starch in Examples 1-5 and Comparative Example 1 was determined. The freeze-thaw stability was characterized by the water separation rate (the water separation rate and freeze-thaw stability are negatively correlated; that is, the lower the water separation rate, the better the freeze-thaw stability). The specific steps were as follows: Prepare a 3% starch solution, boil it in a water bath for 15 min, then freeze 8 mL of the starch solution at -18℃ for 24 h. After thawing at room temperature, centrifuge at 5000 rpm for 15 min, measure the mass of the precipitate, and calculate the mass ratio of the separated supernatant to the starch solution, i.e., the water separation rate. The specific formula is as follows: SVY = (M m) / M×100%; In the formula: SVY represents the water separation rate (%), M represents the mass of 8 mL starch solution (g), and m represents the mass of precipitate (g).
[0069] The results are as follows Figure 7 As shown.
[0070] Depend on Figure 7It can be seen that the water separation rate of starch exhibits a significant "U"-shaped change with the increase of ultra-high pressure treatment. Compared with Comparative Example 1, the water separation rate of Example 5 is significantly reduced, from 16.65% to 8.68%, indicating that DHPM can significantly improve the freeze-thaw stability of acorn starch. Under ultra-high pressure treatment of 100-500 MPa, the water separation rate further decreases to 6.86%-7.92%, indicating that DHPM coupled ultra-high pressure treatment improves the stability of the gel network and further improves the freeze-thaw stability of acorn starch. After being subjected to ultra-high pressure of 600 MPa, the water separation rate soared to 30.62%, far exceeding that of Comparative Example 1. At this point, although starch has a large number of hydrophilic hydroxyl groups and the best water-holding capacity, high-pressure induced recrystallization produces a large number of ordered microcrystals. During cooling and storage, linear and amylopectin molecules are very easy to reassociate through hydrogen bonds, and the starch gel network shrinks rapidly. At the same time, the starch sample is a super-large compacted agglomerate with poor internal water absorption pore connectivity, which cannot stably bind free water. During freeze-thaw cycles, the network shrinks and squeezes out a large amount of free water, ultimately resulting in a significant increase in water separation rate and deterioration of freeze-thaw stability. This trend is consistent with the results of high RVA regression value and high XRD crystallinity.
[0071] 8. The gelatinization characteristics of the natural or modified acorn starch in Examples 1-5 and Comparative Example 1 were determined. The specific steps were as follows: The moisture content was measured using a rapid moisture analyzer. Based on the moisture content of each starch group, the required starch mass and water volume were calculated. 3.0 g of sample (on a dry basis) was mixed with 25 mL of distilled water and placed in an RVA 4500 rapid viscometer. The conditions were set as follows: 50°C for 1 min, then increased to 95°C within 3.5 min and held for 3 min, then decreased to 50°C within 3.5 min and held for 2 min. The viscosity change curve of the sample during this process was recorded. The results are shown below. Figure 8 As shown in Table 2.
[0072] Table 2 Characterization of the gelatinization properties of starches prepared in Examples 1-5 and Comparative Example 1
[0073] It should be noted that different lowercase letters in the same column of Table 2 indicate significant differences. P <0.05.
[0074] Starch gelatinization involves processes such as granule swelling, polysaccharide secretion, and granule breakage. The gelatinization characteristics of starch are key factors determining the textural quality and shelf life of starch products. Figure 8It can be seen that both high-pressure treatments significantly altered the gelatinization behavior of starch and exhibited a clear pressure dependence. Specifically, the peak viscosity showed a trend of first increasing and then decreasing with increasing ultra-high pressure: at 500 MPa, the peak viscosity reached its maximum value, significantly higher than that of Comparative Example 1; while at 600 MPa, the peak viscosity dropped sharply to its minimum value.
[0075] The disintegration value reflects the stability of starch hot paste. The higher the disintegration value, the easier the starch paste is to break down and the worse its heat resistance during heating and stirring. Its trend is similar to that of peak viscosity. As shown in Table 2, the disintegration value is the highest at 500 MPa pressure, indicating that the intermolecular forces of starch are weakened at this time, and it is easier to break under thermal shear. At 600 MPa pressure, the disintegration value drops sharply to the lowest level, and the retrogradation value rises to 2355.67 cP. At this time, the starch undergoes high-pressure induced recrystallization, and the density of intermolecular hydrogen bond crosslinking is greatly increased, forming a stable molecular network that is not easy to break under thermal shear. Therefore, the disintegration value drops sharply. However, during the cooling stage, the randomly stacked short starch chains have a high degree of freedom of movement and are very easy to associate in an orderly manner to form microcrystals, resulting in a significantly higher retrogradation value than the other groups. This result is consistent with the results of DSC high melting temperature and XRD high crystallinity.
[0076] 9. The thermodynamic properties of the natural or modified acorn starch in Examples 1-5 and Comparative Example 1 were determined. Differential scanning calorimetry (DSC) was used to determine the thermodynamic properties of acorn starch (specifically, the energy change during the process of the starch crystal structure being destroyed by heat and dispersed in water to form a hydrophilic colloidal system). The specific steps were as follows: 5 mg of acorn starch and 10 μL of pure water were weighed, compressed into tablets, sealed, and placed in a refrigerator at 4 °C for 24 h. Then, DSC tests were performed. The measurement parameters were: scanning temperature 20-100 °C, heating rate 10 °C / min, and nitrogen gas flow rate 50 mL / min. The results are shown in Table 3.
[0077] Table 3. Characterization of the thermodynamic properties of starches prepared in Examples 1-5 and Comparative Example 1.
[0078] It should be noted that different lowercase letters in the same column of Table 3 indicate significant differences. P <0.05.
[0079] As shown in Table 3, with the increase of ultra-high pressure treatment, the initial gelatinization temperature (To), peak temperature (Tp), and termination temperature (Tc) generally show a trend of first slightly decreasing and then significantly increasing. Within the ultra-high pressure range of 100-500 MPa, the gelatinization temperature range decreases slightly, and the enthalpy (ΔH) gradually decreases from 11.39 J / g in Comparative Example 1 to 5.15 J / g, indicating that ultra-high pressure treatment destroys some unstable microcrystalline structures and reduces the energy required for gelatinization. However, under 600 MPa ultra-high pressure, To, Tp, and Tc all increase significantly, and ΔH drops sharply to 1.24 J / g. While an increase in temperature usually indicates more stable crystals, a decrease in enthalpy indicates fewer crystals. This seemingly contradictory result actually reveals the special characteristics of the 600 MPa treatment. The extremely low ΔH indicates that most of the natural crystals have been destroyed; while the extremely high gelatinization temperature indicates that the remaining small amount of crystals or newly formed rearranged structures have extremely high thermal stability, requiring even higher energy to destroy. Furthermore, the aforementioned infrared results show that the 600 MPa treatment leads to the removal of some bound water. The lack of water often significantly increases the tightness of the reassociation between starch molecular chains, forming dense crystals in anhydrous or low-water states. This is also an important reason for the abnormal increase in its melting temperature. At this point, most of the starch has lost its ability to form a high-viscosity paste, and the remaining stable structure is difficult to fully swell at conventional gelatinization temperatures. This is consistent with the low peak viscosity of RVA under 600 MPa ultra-high pressure treatment.
[0080] In summary, DHPM coupled with ultra-high pressure composite modification can precisely control the crystallinity and particle structure of acorn starch, thereby enabling targeted control of its water-holding properties and freeze-thaw stability. It can also be used to prepare high-stability, high-water-holding, or low-aging modified acorn starch according to application requirements, providing a new technical approach for the high-value utilization of acorn starch resources.
[0081] The above are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the patent protection scope of the present invention.
Claims
1. A method for modifying acorn starch, characterized in that, The method for modifying acorn starch includes the following steps: S1. Provide acorn starch; S2. Mix the acorn starch with water to obtain a starch milk; S3. The starch milk is subjected to dynamic high-pressure microjet treatment, centrifuged and dried to obtain modified acorn starch.
2. The method for modifying acorn starch as described in claim 1, characterized in that, Step S3 includes: S31. The starch milk is subjected to dynamic high-pressure microjet treatment, centrifuged and dried to obtain the first starch. S32. Mix the first starch with water to obtain a starch suspension; S33. The starch suspension is subjected to ultra-high pressure treatment and dried to obtain modified acorn starch. The pressure P of the ultra-high pressure treatment is in the range of 0 MPa < P < 600 MPa.
3. The method for modifying acorn starch as described in claim 2, characterized in that, In step S33, the pressure P of the ultra-high pressure treatment is in the range of 300MPa < P < 600MPa.
4. The method for modifying acorn starch as described in claim 2, characterized in that, In step S31: The pressure of the dynamic high-pressure microjet treatment is 75~85MPa; The dynamic high-pressure microjets treatment time is 3-10 min; and / or, The dynamic high-pressure microjet treatment is performed 1 to 5 times.
5. The method for modifying acorn starch as described in claim 2, characterized in that, In step S32, the starch in the starch suspension has a mass fraction of 15% to 25%.
6. The method for modifying acorn starch as described in claim 2, characterized in that, In step S33: The ultra-high pressure treatment time is 0.5~1.5h; and / or, The drying temperature is 35~45℃.
7. The method for modifying acorn starch as described in claim 1, characterized in that, In step S2, the starch in the starch milk has a mass fraction of 8% to 12%.
8. The method for modifying acorn starch as described in claim 1, characterized in that, Step S1 includes: S11. Provide acorns, grind the acorns into powder, soak them in water, take the sedimentation layer, and obtain the first acorn powder; S12. Soak the first acorn powder in water at 45℃~50℃, take the sedimentation layer, and obtain the second acorn powder. S13. The second acorn powder is soaked in sodium carbonate solution and hydrogen peroxide solution in sequence, and the sediment layer is collected to obtain the third acorn powder. S14. Soak the third acorn powder in water, centrifuge, and dry to obtain the acorn starch.
9. The method for modifying acorn starch as described in claim 8, characterized in that, In step S11, the soaking in clean water is performed 2-3 times; and / or, In step S12, the soaking time in clean water is 12-24 hours; and / or, In step S13, the concentration of the sodium carbonate solution is 0.4%~0.6%, and the soaking time with the sodium carbonate solution is 4~12 hours; and / or, In step S13, the concentration of the hydrogen peroxide solution is 0.8-1.2%, and the solution is used to soak the patient at 35-45°C for 4-5 hours; and / or, In step S14, the soaking time in clean water is 10-12 hours.
10. An acorn starch, characterized in that, The acorn starch is prepared by the acorn starch modification method as described in any one of claims 1 to 9.